Divorce, separation, and remarriage the transformation of family - Gianesini, Giovanna; Blair, Sampson Lee. (Bingley, U.K. : Emerald, 2016)
While the family remains a core social institution in every society, it is, nonetheless, an institution which continues to evolve. In many societies, divorce, separation, and remarriage have become a normative part of marriage and family life. These changes have, understandably, led to a great diversification of the behaviors, attitudes, and norms concerning marriage and family. In order to better comprehend these issues, this multidisciplinary volume of CPFR addresses topics including: marital instability, cohabitation and remarriage, step-parenting, divorce in later life, impact of divorce and separation on children, employment and the risk of divorce, marital dissolution and health, the role of extended kin in the process of divorce, the quality of relationships with former spouses, race/ethnicity and remarriage, economic factors and divorce/remarriage, and extra-marital affairs, among others.
A profile of later life marriages: comparisons by gender and marriage order / Teresa Cooney, Christine Proulx, Linley Snyder-Rivas -- Salient themes of remarriage in the'young-old<U+201d> years / Nicole Graves -- Mothers' dating after divorce / Edward Anderson, Michael Langlais, Shannon Greene -- Exploring the complexity of stepgrandparent-stepgrandchild relationships / Ashton Chapman, Caroline Sanner, Lawrence Ganong, Marilyn Coleman, Luke Russell, Youngjin Kang, Sarah Mitchell -- The role of stepfathers in families receiving support from child protective services / Claudine Parent, Caroline Robitaille, Marie-Christine Fortin, Anne Avril -- Factors affecting adolescent risk-taking in stepfather families / Cassandra Dorius, Karen Benjamin Guzzo -- Consequences of parental divorce during the transition to adulthood: the practical origins of ongoing distress / Mick Cunningham, JaneLee Waldock -- Divorcing commitment: examining the role of parental divorce in undergraduates' friends with benefits relationships / Christina Scott, Joanne Hash, Phoebe Stevens, Tiffani Tejada -- Exploring how parental divorce provides meaning to personal development and interpersonal experiences among emerging adult women / Kayla Reed, Trent Parker, Mallory Lucier-Greer, Marsha Rehm -- Coparenting in the digital era: exploring divorced parents' use of technology / Jodi Dworkin, Ellie McCann, Jennifer McGuire -- Social research of divorce in USSR and Russia / Vladimir Solodnikov -- Influence of work obligations on family commitment among couples in private sector in Kwara State / Olufemi Fawole, Oluwakemi Ogunbowale -- The extended family: disharmony and divorce in Korea / Yean-Ju Lee -- Marital status and the influence of emphasized femininity on the romantic relationships of Tamil single mothers in Malaysia / Premalatha Karupiah -- The prevalence and determinants of remarriage in Bangladesh / Mohammad Islam, Mohammad Hasan, Mohammad Hossain, Tehminal Ghafur.
Includes bibliographical references.
Print version record
Keywords: Social Science -- Sociology / Marriage & Family; Sociology: family & relationships; Divorce; Remarriage